2018
DOI: 10.1039/c7nj04223j
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of curcumin complexes with iron(iii) and manganese(ii), and effects of curcumin–iron(iii) on Alzheimer's disease

Abstract: Plants provide a wealth of bioactive compounds which aid in exerting a substantial strategy for the treatment of neurological disorders such as Alzheimer's disease and dementia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…In another research, Paramera et al determined the stability of yeast cellloaded curcumin, it showed that yeast cells restricted the curcumin from environmental factors (i.e., light, humidity, and heat) (Paramera et al, 2011b). Curcumin prepared with Mn (II) and Fe (III) salts exhibited potent activity to Alzheimer's disease in Swiss albino male rats (Bicer et al, 2018). Palladium (II) complexes with curcumin synthesized had exhibited a strong antitumor effect to MCF-7, HeLa, and A549 tumor cells (Li et al, 2018).…”
Section: Nanospheres and Microcapsulesmentioning
confidence: 99%
“…In another research, Paramera et al determined the stability of yeast cellloaded curcumin, it showed that yeast cells restricted the curcumin from environmental factors (i.e., light, humidity, and heat) (Paramera et al, 2011b). Curcumin prepared with Mn (II) and Fe (III) salts exhibited potent activity to Alzheimer's disease in Swiss albino male rats (Bicer et al, 2018). Palladium (II) complexes with curcumin synthesized had exhibited a strong antitumor effect to MCF-7, HeLa, and A549 tumor cells (Li et al, 2018).…”
Section: Nanospheres and Microcapsulesmentioning
confidence: 99%
“…The results showed that CRANAD‐17, a curcumin scaffold, reduced Aβ fibril formation, inhibited the aggregation of Aβ42, and prevented the β42 cross‐linking induced by Cu 2+ . Likewise, in vivo studies of the metal complex of curcumin with Fe 3+ have demonstrated a reduction in the accumulation of Aβ 25‐35 and strengthened the memory of rats compared to a curcumin‐Mn 2+ complex and curcumin alone (Fig. ).…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Moreover, the side chain carboxyl group of heme may interact with one the hydroxyl groups of curcumin. 24,25…”
Section: Quantitative Methodsmentioning
confidence: 99%